Kadar Vitamin D dan Kejadian Preeklamsi Berat Awitan Lambat - Lestari, Lara Santi Indah; Hilmanto, Dany; Anwar, Anita Deborah (FORUM ILMIAH KESEHATAN, 2023)
Preeclampsia is one of the main contributors to the high maternal mortality rate in Indonesia. Meanwhile, it is suspected that vitamin D deficiency was one of the triggers of the occurrence of slow onset preeclampsia. Then research is needed aimed at analyzing the relationship between vitamin D levels and the incidence of slow onset preeclampsia. The design of this study was a case control with 30 respondents for each group, who were patients visiting Dr. Slamet Hospital, Garut. The diagnosis of normal pregnant women and pregnant women with slow onset preeclampsia was obtained from the anamnesa form, and vitamin D levels were examined using the CMIA method (Chemiluminescent Microparticle Immunoassay). The results of the data analysis indicated the value of P = 0.028. It was concluded that there was a relationship between vitamin D levels and the incidence of slow seizure preeclampsia.Keywords: vitamin D; severe preeclampsia; slow onset ABSTRAK Preeklamsi merupakan salah satu penyumbang utama tingginya angka kematian ibu di Indonesia. Sementara itu diduga kekurangan vitamin D menjadi salah satu pencetus terjadinya preeklamsi berat awitan lambat. Maka diperlukan penelitian yang bertujuan menganalisis hubungan antara kadar vitamin D dengan kejadian preeklamsi berat awitan lambat. Rancangan penelitian ini adalah case control dengan 30 responden untuk masing-masing kelompok, yang merupakan pasien yang berkunjung ke RSU Dr. Slamet Garut. Diagnosa ibu hamil normal dan ibu hamil dengan preeklamsi berat awitan lambat didapatkan dari formulir anamnesa, dan kadar vitamin D diperiksa menggunakan metode CMIA (Chemiluminescent Microparticle Immunoassay). Hasil analisis data menunjukkan nilai p = 0,028. Disimpulkan bahwa ada hubungan antara kadar vitamin D dengan kejadian preeklamsi berat awitan lambat.Kata kunci: vitamin D; preeklamsi berat; awitan lambat